Pengaruh Kinerja KeuanganTerhadap Return Saham (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2012-2014) - Elsa Saputriyanti Butarbutar, 12.05.52.0054; Aini, Nur (Students Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the effect of the Return On Asset (ROA), Return on Equity (ROE), Net Profit Margin (NPM), the Current Ratio (CR), and Debt to Equity Ratio (DER) to Return Shares in the company sector listed on the Indonesia Stock Exchange (BEI) in 2012 to 2014. the sample was determined by purposive sampling method, to obtain a sample of 361 manufacturing companies. The data used in this research is secondary data. Analysis of the data used is multiple regression analysis. The research proves that (1) return on assets is not no effect on stock returns, (2) return on equity has no effect on stock returns, (3) net profit margin has no effect on stock returns, (4) current ratio positive and significant effect on stock returns, and (5) debt to equity ratio and significant positive effect on stock returns. Â Keywords: Return On Asset, Return On Equity, Net Profit Margin, Current Ratio, Debt to Equity Ratio, and Retun Saham